1996
DOI: 10.1056/nejm199601113340216
|View full text |Cite
|
Sign up to set email alerts
|

Single-Day Praziquantel Therapy for Neurocysticercosis

Abstract: Study about the relation between aspirin use and the risk of colorectal cancer (Sept. 7 issue), 1 a key question was whether the investigation inadvertently identified women who were resistant to colorectal cancer. A number of potentially confounding factors, including family history of colorectal cancer, smoking history, alcohol consumption, diet, and level of physical activity, were considered in the data analysis. Unaddressed was the effect of hormone-replacement therapy on the risk of colorectal cancer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 3 publications
1
23
0
2
Order By: Relevance
“…On this basis, it has been suggested that if parenchymal brain cysticerci are exposed to high concentrations of praziquantel maintained for up to 6 hours (three doses of 25-30 mg/kg at 2-hour intervals on a single day), this might be sufficient to destroy the parasites. 10 Preliminary results are encouraging. The decrease in the number of cysts visualized on neuroimaging studies after a 1-day therapy is similar to that observed in patients receiving longer courses of the drug at conventional doses.…”
Section: Cysticidal Drugsmentioning
confidence: 93%
See 1 more Smart Citation
“…On this basis, it has been suggested that if parenchymal brain cysticerci are exposed to high concentrations of praziquantel maintained for up to 6 hours (three doses of 25-30 mg/kg at 2-hour intervals on a single day), this might be sufficient to destroy the parasites. 10 Preliminary results are encouraging. The decrease in the number of cysts visualized on neuroimaging studies after a 1-day therapy is similar to that observed in patients receiving longer courses of the drug at conventional doses.…”
Section: Cysticidal Drugsmentioning
confidence: 93%
“…The decrease in the number of cysts visualized on neuroimaging studies after a 1-day therapy is similar to that observed in patients receiving longer courses of the drug at conventional doses. 10,17,39,46 Albendazole is another strong cysticidal drug, initially tested at doses of 15 mg/kg/day for a 1-month period. 28 It was later found, however, that at similar doses the length of therapy could be shortened to 1 week without lessening the drug efficacy.…”
Section: Cysticidal Drugsmentioning
confidence: 99%
“…This treatment regimen has been demonstrated to be successful in singlecysticercus disease, but unfortunately efficacy could not be demonstrated in patients with multiple cysticerci which represent the major phenotype in sub-Saharan Africa. 87,88 Follow-up of patients and monitoring of treatment success represents another challenge. The CT scanner may not be functional anymore or the financial constraints may be too high.…”
Section: Difficulties Of Treating Ncc In Sub-saharan Africamentioning
confidence: 99%
“…Initial studies with praziquantel noted that doses as low as 5 to 10 mg/kg/day had some effect against cysts, and doses as high as 50 to 75 mg/kg/day were well tolerated. A dosage of 50 mg/kg/day for 2 weeks was adopted by most subsequent studies (11, 13, 16, 29, 32, 59, 63, 67, 68, 71, 94-96, 98, 103, 111), although a single-day regimen of praziquantel has recently been described (24,25,35,69,80,81), with similar rates of cyst disappearance in some groups of patients. No dose ranging studies were performed with albendazole in cysticercosis.…”
Section: Vol 15 2002 Guidelines For Treatment Of Neurocysticercosismentioning
confidence: 99%